New molecular targets for PET and SPECT imaging in neurodegenerative diseases - Benadiba,Marcel (2012)
The pathophysiology of neurodegenerative diseases (ND) such as Alzheimer's disease (AD) and Parkinson's disease (PD) has not yet been completely elucidated. However, in the past few years, there have been great knowledge advances about intra-and extracellular proteins that may display impaired function or expression in AD, PD and other ND, such as amyloid beta (Aβ), α-synuclein, tau protein and neuroinflammatory markers. Recent developments in the imaging techniques of positron emission tomography (PET) and single photon emission computed tomography (SPECT) now allow the non-invasive tracking of such molecular targets of known relevance to ND in vivo. This article summarizes recent findings of PET and SPECT studies using these novel methods, and discusses their potential role in the field of drug development for ND as well as future clinical applications in regard to differential diagnosis of ND and monitoring of disease progression.